O uso do aplicativo de mensagens Whatsapp e a percepção de seus reflexos na comunicação interna e na cultura organizacional no órgão X - Etcheverry, Susana Beatriz Alvis (2019)
Within the context in which relationships are becoming more mediatized, this research has the aim of analyzing the perceptions about using – in a scope of work – the app of instant messages WhatsApp Messenger installed in mobile devices (smartphones) and its reflexes on the internal communication and the institutional culture of Organization X. The objectives that guide this work were analyzing the perceptions of the way WhatsApp is used inside the Organization X and investigating whether the WhatsApp use is perceived with impact on the internal communication routines of Organization X. To reach these goals it was conducted an exploratory research of qualitative approach. The technique of data collection used was a semi structured interview, with the script based on the Cognitive Operators of Complex Thought (Mariotti, 2007). The non-probability sample was for convenience made of the Organization X leaders. The information and data collected were analyzed by the Textual Discursive Analysis technique (Moraes, 2003). The results of the research indicated to the perception that WhatsApp is consolidating itself as the most agile way of promoting internal communication, and that its use has reflexes on the institutional culture as well.